Inflammatory burden index as a prognostic marker in patients with advanced gastric cancer treated with neoadjuvant chemotherapy and immunotherapy - Huang, Jiao-Bao; Zhou, Zhi-Yong; Lu, Jun; Zhu, Ji-Yun; Lai, Bin; Mao, Sheng-Xun; Cao, Jia-Qing (Frontiers in Immunology, 2025)
BackgroundBlood inflammation index has been shown to correlate with the prognosis of patients with gastric cancer. However, few studies have compared the efficacy of existing blood inflammatory markers in predicting the prognosis of patients with locally advanced gastric cancer in combination with neoadjuvant chemotherapy and immunotherapy.ObjectiveThe objective of this study was to compare the prognostic value of existing commonly used blood inflammatory index in patients with advanced gastric cancer treated with neoadjuvant chemotherapy combined with immunotherapy.MethodsThe clinicopathological data of patients with advanced gastric cancer from three centers in China were analyzed retrospectively. Univariate COX regression analysis was used to analyze the independent risk factors of poor tumor regression and overall survival (OS) in this part of patients, and the predictive value of different inflammatory indexes on prognosis was compared by C-index index. Finally, Inflammatory burden index(IBI) was grouped by X-tile software, and Kaplan-Meier method was used to compare the survival difference between groups.ResultsA total of 163 patients were enrolled in this study. The median age was 63 years(56-68). The median cycle of neoadjuvant therapy was 4(3-4). The median survival time was 85.1%(1 years), 65.6%(2 years), and 47.4%(3 years).Univariate analysis showed that IBI was an independent risk factor for non-TR(residual tumor cells>50%) (HR=1.08,95%CI:1.00-1.45,p<0.001)and OS(HR=1.04,95%CI:1.03-1.05,p<0.001). IBI is the best predictor of OS (C-index: 0.82, 95% CI: 0.78-0.87) among all inflammatory indexes. The IBI cutoff value was 52.1. It was found that the high IBI group had a higher incidence of postoperative complications(32.1%vs14.3%, p=0.001), the proportion of non-TR patients was significantly higher than that of the low IBI group(64.3%vs35.7%, p =0.001), and the high IBI group had a significantly lower OS((47.6% vs 87.6%, p < 0.001).ConclusionIBI is the best inflammatory index to predict the prognosis of advanced gastric cancer treated with neoadjuvant chemotherapy combined with immunotherapy, which will help guide patients’ treatment decisions. This result still needs to be verified by large prospective studies.